Objectively measured physical activity according to the periods of the day in the Pelotas Cohort - Andrea Wendt; Fernando C. Wehrmeister; Luiza I. C. Ricardo; Bruna Gonçalves C. da Silva; Rafaela C. Martins; Helen Gonçalves; Felipe F. Reichert; Inácio Crochemore-Silva (Revista Brasileira de Atividade Física e Saúde)
This study aims to describe objectively measured physical activity (PA) in different periods of the day in young adults according to sex, socioeconomic position and during weekdays and weekends. This is a cross-sectional analysis carried out with the participants of the 1993 Pelotas Birth Cohort at 22 years. PA was assessed by triaxial accelerometer. Descriptive analyses were performed presenting the time spent on light PA (LPA) and bouted moderate to vigorous PA (MVPA) in different periods of the day (morning - 6am to 11:59 am, afternoon – 12pm to 7:59 pm and night – 8pm to 11:59pm). The present study included 2,766 individuals (48.2% male and 51.8% female). LPA was higher among women, while bouted MVPA levels were higher among men. The median of  PA was higher on weekdays compared to weekends for all intensities. The bouted MVPA medians in the morning and at night were zero minutes for all days and both sexes. The richest group presented a higher percentage of individuals with zero minutes. PA may vary according to different periods of the day and intensity. The absence of PA practice was markedly influenced by sex and socioeconomic position.